Bahasa Inggris - Ika Puspita Kristianti (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2023)
This study aims to analyze the effect of board gender diversity on environmental, social, and governance (ESG) disclosure in Indonesia, an emerging market. Companies. This study analyzed 58 sample companies that are members of the ESG Leader Index and the IDX Kehati ESG Quality 45 Index. Based on regression analysis, the data results show that the proportion of women on the board of directors significantly reduces the company's ESG risk level. The industrial sector and the market capitalization of the company's stock also strengthen the influence of board gender diversity on the company's ESG risk level. Thus, the industrial sector contributes to the company's follow-up in designing organizational structures and implementing ESG initiatives. The higher the level of capitalization of a company's stock, the greater the company's initiative in increasing the proportion of women on the board of directors to meet the diversity requirements, thereby reducing the level of ESG risk. This study contributes to the limited but growing literature on ESG reporting quality and board gender diversity, especially in emerging economies.